The Ignored Skill in EFL Context “Listening”: A Review of Selected Article by Omar Gokhan Ulum - Yunira, Sandra (Universitas Lancang Kuning, 2019)
This paper aimed at reviewing the selected article entitled “The ignored Skill in EFL Context” written by Omer Gokhan Ulum. This study sees Ulum’s article as a unique study and essential to explore the difficulties of listening comprehension faced by students of the first-year university with elementary level English. Ulum’s research involved 50 EFL students from three different classes. The data was accumulated by interview and a set of questions. The outcome of the study showed that EFL students find it hard to understand the listening when people speak with numerous and uncommon accents. Also, the students do not have the skill to understand the meanings of words which are not pronounced accurately. This present study concluded that the students’ inability to quickly memorize the words or sentences that they have just overheard is highly likely to be the reason why the listening skill is considered as an ‘annoyance’ for the EFL students in the study. These results may help EFL teachers in boosting students’ listening comprehension skills. As an outcome, this present paper may say that Ulum’s article can be replicable onto similar research topics, especially on the methodology section.